An Experimental and Theoretical Investigation on Pentacoordinated Cobalt(III) Complexes with an Intermediate S=1 Spin State: How Halide Ligands Affect their Magnetic Anisotropy. Issue 3 (14th December 2015) - Brazzolotto, Deborah; Gennari, Marcello; Yu, Shengying; Pécaut, Jacques; Rouzières, Mathieu; Clérac, Rodolphe; Orio, Maylis; Duboc, Carole
Abstract: Invited for the cover of this issue are the groups of Maylis Orio at the Aix‐Marseille University and Carole Duboc at the University of Grenoble Alpes. The image depicts the magnetic behavior dependence to the halide nature in Co III species represented by ribbons as "double‐well" diagrams, which are traditionally used to depict magnetization processes. Read the full text of the article at10.1002/chem.201502997 . Abstract : " The magnetic anisotropy of these complexes, the zero field splitting parameter (D), shows a dependence on the nature of the halide: the largest D value was obtained for the chloride compound and the smallest for the iodide one ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 925 ff. (DOI:10.1002/chem.201502997 ).